Online corporate communication: Should national culture matter? - Capece, Guendalina; Di Pillo, Francesca (Frontiers in Communication, 2023)
Although the Internet constitutes a global phenomenon, cultural filters influence its use at the local level, ultimately determining a more or less favourable attitude towards a given website. The purpose of this paper is to investigate how the culture of a nation influences corporate website usability. In order to assess how cultural differences impact web design, two countries that are at opposite cultural poles have been chosen: India and Australia. A content analysis technique was used to code the cultural markers and new indicators have been created to allow the association of the graphic elements and the contents of the websites with the cultural characteristics proposed by Hofstede and Hall frameworks. This work provides a guideline for companies, analysts, and the different professionals involved in online communication and web design. More specifically, they have to be aware of the cultural challenges when they operate outside the national boundaries, by designing a culturally usable website in one of the countries chosen for this study.